0385 Risk Assessment of Sleep Disorder Comorbidity Across Active Duty Army Installations from Military Medical Databases. (27th May 2020) - Brager, A J; Hosamane, N; Capaldi, V; Simonelli, G
Abstract: Introduction: The impact of sleep disorders on active duty Soldiers' medical readiness is clinically significant. Sleep disorders present high comorbidity with disease states directly impacting medical readiness, ranging from musculoskeletal injury (MSK-I), obesity, and drug dependence. The current study performed a risk assessment of sleep disorder comorbidity with MSK-I, obesity, and drug dependence across active duty United States Army installations. Methods: Health incidences (percent active duty per installation) were queried from the Office of the Surgeon General Health of the Force (HoF) report, specifically for Fiscal Year (FY) 2017 (n = 471, 000; 85.5% male, > 70% between 18 -34). Nonparametric ranked tests identified active duty Army installations at low risk (green; < 25% percentile relative to mean rank), moderate risk (amber; 25% - 50%), and high risk (red; > 75% percentile). Linear regressions determined extent of comorbidity of sleep disorders with MSK-I, obesity, and drug dependence (tobacco use and substance abuse). Results: Mean rank comparisons for sleep disorders vs. injury index (p=0.499), obesity (p=0.306), tobacco use (p=0.378), and substance abuse (p=0.591) did not differ for each installation. Further, there was a high degree of co-morbidity for mean percentage of diagnosed sleep disorder with injury index (p<0.001; r 2 = 0.517), obesity (p<0.001; r 2 = 0.963), tobacco use (p<0.001; r 2 = 0.928), and substance abuse (p<0.001; r 2 = 0.968). Conclusion: In general, large infantry and artillery training units located in the Southeastern United States were "in the red" for not meeting medical readiness standards. A few exceptions include Virginia-Maryland triangle, a heavily populated area. These data demonstrate strong geographical influences on health risk comorbidity in active duty Soldiers comparable to civilian sectors. Support: Military Operational Medicine Research Program